Educational sponsorship - Hardie, Joshua (Henry Stewart Talks, 2009)
What is educational sponsorship?, Corporate social responsibility and cause related marketing, Why invest in education?, Return on reputation, Employee pride and advocacy, Local media, Young people as advocates, Business involvement in schools, Who benefits?